An Assessment of contributing factors affecting student nurses compliance with the RLE guidelines of three selected schools of nursing in metro manila : basis for a proposed nursing student handbook - Defino, Lorna M. (Manila : National University, 2011)
This study is significant in a way that it aims to improve discipline among students, specifically the student nurses by identifying the factors contributing to their compliance. The research seeks reasons why despite of yearly orientations and tangible visualizations in bulletin boards, there was still a large number of students who do not comply with the policies.
Title page -- Approval Sheet -- Acknowledgement -- Table of contents -- List of tables / figures -- Abstract -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature -- Chapter 3. Research Methodology -- Chapter 4. Presentation, Analysis, and Interpretation of Data -- Chapter 5. Summary, Conclusion, and Recommendation -- Bibliography -- Appendices -- Curriculum Vitae.
Research Method : Descriptive Method.
Includes bibliographical references.